Nanodot-doped peptide hydrogels for antibacterial phototherapy and wound healing. (20th December 2021) - Wang, Xuan; Qiu, Lin; Wang, Cheng; Gao, Zihan; Zhou, Shuwen; Cui, Pengfei; Jiang, Pengju; Hu, Huaanzi; Ni, Xinye; Du, Xuancheng; Wang, Jianhao; Xia, Jiang
Abstract : Antimicrobial peptide hydrogels combined with phototherapy in the treatment of infected wounds. Abstract : Bacterial infection of wounds delays the healing process, increases the risk of chronic trauma associated with pain and complications, and offers a breeding ground for drug-resistant bacteria. A rapid and effective eradication of the bacterial species in the wound area is thus important. Herein, we designed a phototherapeutic antibacterial platform based on peptides and copper sulfide nanodots (CuS NDs) for multi-mechanistic eradication of bacteria colonized on the wound surface. The antimicrobial peptide weaves into a network in the form of a hydrogel, which supports CuS NDs to generate heat and produce reactive oxygen species (ROS) under the irradiation of near-infrared light (NIR). The heat and ROS generated in situ act as non-contact-based antibacterial factors and together with contact-based antimicrobial peptides cause irreversible membrane destruction, cell content damage, and thermal ablation of the bacteria. Lastly, nanodot-doped peptide hydrogels combined with collagen showed complete bacterial elimination and significantly accelerated wound healing in a splint-fixed mouse infection model.